Study Of Corn Biology In Agriculture And The Technology Of Its Cultivation - Kholdarova Sevarakhon Rakhmatjon qizi; Masardinov Khushnudbek Bozorboy ogli; Fayzullayeva Mubinakhon Utkirbek qizi (Research Parks Publishing LLC, 2021)
The study of the biology of corn in agriculture, which allows to obtain high yields from this plant, as well as the correct organization of cultivation technology, efficient usa of land